"Why Try? Comparing the Aims of Parties and Amici in U.S. Supreme Court Litigation". (2nd April 2020) - Wofford, Claire B.
Abstract: Why do litigants and amici curiae appeal to the U.S. Supreme Court? The judicial politics literature tells us that litigants do so primarily to win the case while amici are more concerned with the legal policy contained in the opinion. The concept of "legal rules" offers one mechanism to evaluate these claims. As legal rules are the Court's legal policy, the extent of resources case participants devote to rules should reflect the extent they care about the case's outcome or policy: the more they care about policy, the more attention they should devote to rules; the more they are interested in winning the case, the less attention they should devote to rules. I measure this attention via the number of legal rules litigants and amici suggest to the justices in their written briefs. The findings confirm that parties care primarily about victory on the merits while amici are generally concerned with policy. The results also indicate, however, that the aims of both litigants and amici can vary significantly by their status and that interest group amici in particular may be more interested in winning a case than we have recognized.